A conceptual framework for CSR analysis: integration of stakeholder theory and institutional theory within the postmodern strategic management. (5th July 2021) - Al-Zoubi, Mohammad Orsan
This paper aims to introduce a contemporary conceptual framework for CSR analysis. Currently, most studies on CSR employ the stakeholder theory and the institutional theory as separate tools rather than being complementary to each other. Therefore, this paper suggests integrating stakeholder theory and institutional theory into strategic management as it constitutes a point of intersection between modern and postmodern eras. In view of that, 'postmodern CSR strategic management' is constructed as a comprehensive framework which provides a bigger picture to CSR analysis than any single theory. The conceptual framework developed in this article can serve as a cornerstone to design and implement a firm's CSR strategy under pressures of stakeholders and institutions that operate at global and local levels. This paper is purely theoretical as the results thereof offer a theoretical foundation for empirical studies relating to CSR practices in postmodern era which is characterised by complexity and multiplicity.